The Preferential Infection of Astrocytes by Enterovirus 71 Plays a Key Role in the Viral Neurogenic Pathogenesis - Feng, Min; Guo, Sujie; Fan, Shengtao; Zeng, Xiaofeng; Zhang, Ying; Liao, Yun; Wang, Jianbin; Zhao, Ting; Wang, Lichun; Che, Yanchun; Wang, Jingjing; Ma, Na; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
The pathological manifestations of fatal cases of human hand, foot and mouth disease (HFMD) caused by enterovirus 71 (EV71) are characterized by inflammatory damage to the central nervous system (CNS). Here, the dynamic distribution of EV71 in the CNS and the subsequent pathological characteristics within different regions of neonatal rhesus macaque brain tissue were studied using a chimeric EV71 expressing green fluorescence protein. The results were compared with brain tissue obtained from the autopsies of deceased EV71-infected HFMD patients. These observations suggested that the virus was prevalent in areas around the blood vessels and nerve nuclei in the brain stem and showed a preference for astrocytes in the CNS. Interestingly, infected astrocytes within the in vivo and in vitro human and macaque systems exhibited increased expression of excitatory neurotransmitters and cytokines that also stimulated the neuronal secretion of the excitatory neurotransmitters noradrenalin and adrenaline, and this process most likely plays a role in the pathophysiological events that occur during EV71 infection.